1994
DOI: 10.1099/00222615-41-4-220
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C RNA prevalence in a Western European organ donor pool and virus transmission by organ transplantation

Abstract: Summary. Liver disease is a common finding after organ transplantation and might in part be due to transmission of hepatitis C virus (HCV). The aim of this study was to determine the prevalence of positive results with different anti-HCV tests and HCV-RNA in a local donor pool and to clarify to what extent HCV was transmitted to organ recipients. Serum samples from 207 consecutive organ donors were analysed retrospectively with anti-HCV ELISA (2nd and 3rd generation), anti-HCV RIBA (2nd generation) and HCV pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…First, there was a concern that grafts with HCV would be damaged and would not perform well after transplantation. Second, there is an obvious risk of transmitting HCV to the recipient through transplantation of the infected graft [51,52]. However, several centers have shown that selected HCV-infected livers may be successfully transplanted into patients with HCV-induced liver disease.…”
Section: Use Of Marginal Donor Liversmentioning
confidence: 98%
See 1 more Smart Citation
“…First, there was a concern that grafts with HCV would be damaged and would not perform well after transplantation. Second, there is an obvious risk of transmitting HCV to the recipient through transplantation of the infected graft [51,52]. However, several centers have shown that selected HCV-infected livers may be successfully transplanted into patients with HCV-induced liver disease.…”
Section: Use Of Marginal Donor Liversmentioning
confidence: 98%
“…In addition, HCV infection is common in the donor pool, with 1.4% to 3% of organ donors testing positive for HCV (by the HCV polymerase chain reaction test) [51,52]. Donor livers infected with HCV have traditionally been discarded for two reasons.…”
Section: Use Of Marginal Donor Liversmentioning
confidence: 99%
“…The prevalence of anti-HCV in potential organ donors in North America and Europe is approximately 2% [36,37], more than five times that in healthy blood donors, reflecting a direct association between high-risk behaviors and premature death. Almost 20% of anti-HCV-positive donors will be RNA negative [38].…”
Section: Donor Is Anti-hcv Positivementioning
confidence: 99%
“…Since the discovery and cloning of HCV [56,57], several studies have documented a risk of HCV infection among recipients of organs from HCV infected donors [58][59][60][61].…”
Section: Hepatitis Cmentioning
confidence: 99%